Exosomal clusterin, identified in the pericardial fluid, improves myocardial performance following MI through epicardial activation, enhanced arteriogenesis and reduced apoptosis. (15th October 2015) - Foglio, Eleonora; Puddighinu, Giovanni; Fasanaro, Pasquale; D'Arcangelo, Daniela; Perrone, Giulietta A.; Mocini, David; Campanella, Ciro; Coppola, Luigi; Logozzi, Mariantonia; Azzarito, Tommaso; Marzoli, Francesca; Fais, Stefano; et al.
Abstract: Background: We recently demonstrated that epicardial progenitor cells participate in the regenerative response to myocardial infarction (MI) and factors released in the pericardial fluid (PF) may play a key role in this process. Exosomes are secreted nanovesicles of endocytic origin, identified in most body fluids, which may contain molecules able to modulate a variety of cell functions. Here, we investigated whether exosomes are present in the PF and their potential role in cardiac repair. Methods and results: Early gene expression studies in 3 day-infarcted mouse hearts showed that PF induces epithelial-to-mesenchymal transition (EMT) in epicardial cells. Exosomes were identified in PFs from non-infarcted patients (PFC) and patients with acute MI (PFMI). A shotgun proteomics analysis identified clusterin in exosomes isolated from PFMI but not from PFC. Notably, clusterin has a protective effect on cardiomyocytes after acute MI in vivo and is an important mediator of TGFβ-induced. Clusterin addition to the pericardial sac determined an increase in epicardial cells expressing the EMT marker α-SMA and, interestingly, an increase in the number of epicardial cells ckit + /α-SMA +, 7 days following MI. Importantly, clusterin treatment enhanced arteriolar length density and lowered apoptotic rates in the peri-infarct area. Hemodynamic studies demonstrated an improvement in cardiac function in clusterin-treated compared to untreated infarcted hearts. Conclusions: Exosomes are present and detectable in the PFs. Clusterin was identified in PFMI-exosomes and might account for an improvement in myocardial performance following MI through a framework including EMT-mediated epicardial activation, arteriogenesis and reduced cardiomyocyte apoptosis.